AI becomes her: Discussing gender and artificial intelligence. Issue 1 (1st June 2019) - Costa, Pedro; Ribas, Luísa
AbstractThis article seeks to understand why femininity seems to be often present in artificial intelligence and tackle the questions that arise when this phenomenon is subject to closer inspection. It draws on a previous study on the relationship between gender and AI, complemented by an analysis of digital assistants such as Alexa, Cortana, Google Assistant and Siri that reveals how these entities tend to be feminized through their anthropomorphization, the tasks that they perform and their behavioural traits. Furthering this discussion, this article addresses current trends of development of digital assistants and their stance towards gender, considering the functions or features that are being prioritized in AI evolution. It then focuses on the main questions raised by researchers and academics when examining the phenomenon and confronts these views with discussions around the feminization of AI in the context of online media coverage. This debate also highlights how common conceptions of AI and its portrayals of gender are influenced by bodies of fiction. Finally, the project Conversations with ELIZA seeks to comment on this phenomenon by ironically exposing and reinforcing common stereotypes and gender assumptions. In this manner, this study seeks to incite reflection on how artificial intelligence is reflecting our social and cultural views back to us.